FAKTOR-FAKTOR YANG MEMPENGARUHI KELULUSAN UJI PRAKTIK ANTENATAL CARE PADA MAHASISWA TINGKAT I SEMESTER II AKADEMI KEBIDANAN - Illa Arinta (JKM (Jurnal Kebidanan Malahayati), 2021)
FACTORS AFFECTING THE GRADUATION OF ANTHENATAL CARE PRACTICE TEST IN LEVEL I SEMESTER II STUDENTS OF MIDWIFERY ACADEMY Background. The success of students in higher education is influenced by several factors, both internal and external. Internal factors are factors that come from students themselves, such as learning motivation, learning attitudes and habits, learning skills, physical condition. External factors are factors that come from outside the students themselves, such as the family, school and community environment. The preliminary survey which was conducted by interviewing 10 students on August 1, 2019, as many as 8 students said that the practice of Antenatal Care is one of the tests that is rather difficult to understand because it was the first experience facing the exam so that the experience of the practical exams that had been carried out had not been described. Students also said that they rarely study independently in the laboratory because the steps to practice antenatal care are difficult to learnPurpose knowing the factors that influence the graduation of antenatal care (ANC) practice in midwifery students semester II at the Midwifery Academy of the Gatot Soebroto Army Hospital in 2019.Method. The research design used was quantitative by using a cross sectional approach, the research location was carried out at the MidwiferFACTORS AFFECTING THE USED OF MAN CONTRACEPTION OPERATION METHOD  Background: The use of operation method of man contraception was still very little used, especially among husbands. Though the male operative method is very effective in terminating pregnancy. Operation method of man contraception was a method with a very high level of effectiveness. So the hoped that method of man contraception choice for couples if they intend to terminate the pregnancy. However, currently the use of method of man contraception is still very small, so it needs hard work to increase the use of method of man contraception. Purpose:The purpose of this study was to determine the dominant factors associated with the use of MOP in Bebetin Village. Methods:This type of research is quantitative research with the independent variables of education, knowledge, attitudes, family support and support from health workers. While the dependent variable is the use of the male operative method. The minimum sample size used was 68 respondents with the sampling technique used simple random sampling. This study used a questionnaire instrument in data collection. Then used enumerators assisted by posyandu and puskesmas in data collection. Analysis using chi-square then multivariate analysis used logistic regression. Result:The results of the study found that there was a relationship between family support and the use of male operation method (AOR: 7.4 95% CI 1.6-33.6) and support from health professionals (AOR: 4.5 95% CI 1.0-20.1). Meanwhile education, attitudes and knowledge are not related to the use of male operation method in Bebetin Village. Conclusion: The conclusion is that family support and health worker support are the dominant factors that husbands want to use male operation methodSuggestion: It is hoped that in the future support for family support and support for health workers will be increased while at the same time increasing the use of male operation method. Keywords : male operative method; contraception; behavior ABSTRAK Latar Belakang: Penggunaan kontrasepsi mantap masih sangat sedikit digunakan khususnya pada kaum suami. Padahal metode operatif pria (MOP) sangat efektif untuk menghentikan kehamilan. Penggunaan MOP merupakan metode dengan tingkat efektifitas yang sangat tinggi. Sehingga harapannya kontrasepsi mantap menjadi pilihan pasangan jika berniat untuk menghentikan kehamilan. Namun saat ini penggunaan MOP masih sangat kecil dilakukan sehingga perlu kerja keras dalam meningkatkan penggunaan MOP.Tujuan: Tujuan dari penelitian ini adalah mengetahui faktor dominan yang berhubungan dengan penggunaan MOP di Desa Bebetin.Metode: Jenis penelitian yang dilakukan adalah penelitian kuantitatif dengan variabel independent pendidikan, pengetahuan, sikap, dukungan keluarga dan dukungan tenaga kesehatan. Sedangkan variabel dependen adalah penggunaan metode operatif pria. Besar sampel minimal yang digunakan adalah 68 responden dengan Teknik pengambilan sampel secara simple random sampling. Penelitian ini menggunakan instrument kuesioner dalam pengumpulan datanya. Kemudian menggunakan enumeroator dibantu posyandu dan puskesmas dalam pengumpulan data. Analisis menggunakan chisquare kemudian analisis multivariat menggunakan regresi logistik.Hasil: Hasil penelitian menemukan bahwa terdapat hubungan dukungan keluarga dengan penggunaan MOP (AOR :7,4 95% CI 1,6-33,6) dan dukungan tenaga kesehatan (AOR :4,5 95% CI 1,0-20,1). Sedangkan pendidikan, sikap dan pengetahuan tidak berhubungan dengan penggunaan MOP di Desa Bebetin.Kesimpulan: Kesimpulannya bahwa dukungan keluarga dan dukungan tenaga kesehatan menjadi factor yang dominan suami mau menggunakan MOP.Saran: Diharapkan kedepannya dukungan keluarga dan dukungan tenaga Kesehatan semakin ditingkatkan sekaligus meningkatkan penggunaan MOP Kata kunci : metode operatif pria; kontrasepsi; perilaku y Academy of RSPAD Gatot Soebroto, with a total sample of 49 female students. Research time from March to August 2019.Univariate and bivariate data analysis using ChiSquare.Result. Evaluation of the ANC practice exam in students is very good with the results of the psychological test still being suggested by 16 respondents 84.2%. The results of most ANC practice exam evaluations are good with health tests fulfilling the requirements as many as 15 respondents 60.0%. The results of the most evaluations of ANC practice exams are good results with 21 respondents 70.0% of the origin majoring in science. Most ANC practice exam evaluation results are with good results with guidance intensity> 3 times as many as 29 respondents 96.7%.Conclusion. ANC practice exam evaluation on students is very good with the results of the psychological test can still be suggested, there is a significant relationship between the ANC practice score and the psychological test. There is no significant relationship between ANC practice scores with health tests, high school majors and intensity of guidance.Suggestions based on the results of the research show that the results of the psychological test have a very significant effect on academic achievement, therefore focusing on increasing the psychological factors of students is the most appropriate effort to improve and or maintain academic achievement. It is suggested to students to further increase their motivation to learn through various ways, including liking each subject presented, having a desire to acquire knowledge and others. Key words: antenatal care, psychology test, students